Correlation between serum magnesium and calcium ions and peripheral nerve function in chronic kidney disease - Zuo Xiao-li; Shang Hong-xue; Wang Yu-juan (Linchuang shenzangbing zazhi)
Objective To explore the ionic levels of serum calcium(Ca2+)and magnesium(Mg2+)in patients with chronic kidney disease（CKD）and examine their correlations with peripheral nerve functions.Methods From October 2011 to October 2019,a total of 300 CKD patients were selected as subjects for this cross-sectional study.According to the glomerular filtration rate,they were divided into 1～5 stages.The serum levels of Ca2+ and Mg2+ were compared among different stages.Sensory and motor conduction latencies,conduction velocities,amplitudes of median and common peroneal nerves were measured and the correlations between parameters and serum levels of Ca2+ and Mg2+ analyzed.Results The serum levels of Ca2+ and Mg2+ in patients with CKD stage 1～3 were significantly higher than those in those with stage 4～5（P<0.05）and the incidence rates of hypocalcemia and hypermagnesemia in CKD stage 1～3 were significantly lower than those in stage 4～5（P<0.05）.The sensory and motor conduction latencies of median and common peroneal nerves in normal blood calcium and hypercalcemia group were lower than those in hypocalcemia group.SNCV and amplitude were higher than those in hypocalcemia group and motor conduction amplitudes of median and common peroneal nerves were higher in hypercalcemia group than those in normal blood calcium group（P<0.05）.The sensory and motor conduction latencies of median and common peroneal nerves were significantly lower in normal blood magnesium and hypermagnesemia groups than those in hypomagnesemia group.And sural nerve conduction velocity（SNCV）and amplitude were higher than those in hypomagnesemia group and motor conduction amplitude of common peroneal nerve was higher in hypermagnesemia group than that in normal blood magnesium group（P<0.05）.The sensory and motor conduction latencies of median nerve and common peroneal nerve of CKD patients were significantly negatively correlated（P<0.05）while SNCV and amplitude significantly positively correlated with serum levels of Ca2+ and Mg2+（P<0.05）.Conclusions CKD patients often have metabolic disorders of serum Ca2+ and Mg2+,which may have adverse effects on peripheral nerve function.